Consumption Efficiency of Wolf and Lynx Spiders, Pardosa pseudoannulata and Oxyopes javanus, on Insect Pests of Asiatic Pennywort - Bumroongsook, S.; Name, J.; Kilaso, M. (International Journal of Agricultural Technology, 2018)
Asiatic pennywort is a plant common to Central and Southeast Asia and is used for folk medicine. The most common predatory spiders found in the Asiatic pennywort growing areas were wolf and lynx spiders, Pardosa pseudoannulata Bösenberg and Strand and Oxyopes javanus Thorell. They were observed the onsuming two important insect pests of pennywort: young pennywort cutworm, Zonoplusia ochreata Walker, 1865 and a leafhopper, Empoascanara alami Ahmed. The consumption efficiency associated with spider sex and starvation condition of these two predatory spiders on the leafhopper and pennywort cutworm was assessed in the laboratory. The results showed that female spiders consumed more leafhoppers and pennywort cutworms than did the males. Both predatory spiders preferred the second larval instar of pennywort cutworm. The female and male of O. javanus consumed 18.07 and 17.11 insects/day, respectively, and P. pseudoannulata 14.39 and 12.18 insects/day, respectively. Starvation for a prolonged food of time did not increase hunger level of the spiders. The use of these two spiders combined, in comparison with O. javanus alone, against leafhoppers was not significant (P>0.05). However, P. pseudoannulata and O. javanus are important components of the natural enemy complex in pennywort and therefore they should be conserved to aid insect control in pennywort.